A 5-Year Review of Senecavirus A in China since Its Emergence in 2015 - Liu, Fuxiao; Wang, Qianqian; Huang, Yilan; Wang, Ning; Shan, Hu (Frontiers in Veterinary Science, 2020)
Senecavirus A (SVA), previously known as Seneca Valley virus, is classified into the genus Senecavirus in the family Picornaviridae. This virus can cause vesicular disease and epidemic transient neonatal losses in swine. Typical clinical signs include vesicular and/or ulcerative lesions on the snout, oral mucosa, coronary bands and hooves. SVA emerged in Guangdong Province of China in 2015, and thereafter gradually spread into other provinces, autonomous regions and municipalities (P.A.M.s). Nowadays more than half of the P.A.M.s have been affected by SVA, and asymptomatic infection has occurred in some areas. The phylogenetic analysis shows that China isolates are clustered into five genetic branches, implying a fast evolutionary speed since SVA emergence in 2015. This review presented current knowledge concerning SVA infection in China, including its history, epidemiology, evolutionary characteristics, diagnostics and vaccines.